Bacterial community changes in strawberry fruits (Fragaria × ananassa variety “Monterey”) from farm field to retail market stands, an indicator of postharvest contamination - Tenea, Gabriela N.; Reyes, Pamela (Frontiers in Microbiology, 2024)
Background: Strawberry (Fragaria x ananassa) fruits are vulnerable to bacterial contamination; some species are pathogenic and can affect human health. Comprehending the bacterial composition and diversity at different ripe stages is a key determinant of the fruit health, productivity, and quality. Methodology: An amplicon metagenomic approach on the 16S rRNA region was used to identify the bacterial diversity in exocarp of fruits collected from a farm field at two ripe stages: breaking (white, phase two) and ripe (red, phase four) and purchased from different retail market stands at ripe (red, phase four, ready-to-eat) stage. Besides, the fruit quality was assessed. Results: Strawberries carries a high microorganisms diversity, with Pseudomonaceae, Yearsiniaceae, and Hafniaceae being the most abundant families across the samples. Among the groups, Pseudomonaceae and Clostridiaceae were the most abundant families at breaking (phase two) and ripe (phase four), whereas Yearsiniaceae, Hafniaceae, Aeromonadaceae, and Streptococcaceae were the most abundant families in the market group. Although samples from group four-field and market were at the same ripe stage, the bacterial species composition was divergent. Serratia spp. were prevalent (above 60%) in samples collected from the market group, and Pseudomonas (above 70%) species were mostly found in the samples collected from the field settings regardless of the phase. Besides, Escherichia coli and Salmonella enterica were detected in the ready-to-eat samples from both the field and the market, while Enterococcus gallinarum was detected in the samples that originated from the market. Interestingly, Shewanella putrefaciens and S. profunda, two human opportunistic pathogens, were detected in the fruits from the market only. According to alpha and beta diversity analyses, strawberry fruits displayed significant differences (P < 0.05) in bacterial communities within the ripe group, with the samples from the market showing the most bacterial diversity. Although we do not directly correlate the quality attributes with bacterial diversity, the results indicated a clear separation between groups according with their ripe stage and origin. Conclusion: This study provides a comprehensive framework of the bacterial diversity throughout the transition from unripe to ripe strawberries which may aid in the development of preventative measures to manage the postharvest contamination.